A knowledge-based process planning system for injection mold - Lim, J.T.; Rho, H.M.; Cho, K.K. (1994)
The goal of this study is to develop a knowledge-based process planning system interfaced with design for injection mold. Mold parts are interactively designed by using feature-based design approach, and then a part feature database is created through a data conversion module. Attribute information of the database is used as an input for the expert process design module and the standard time estimation module of the knowledge-based process planning system developed in this study. In this developed system, decision making of process design is performed by rules which were acquired from experienced process planners through interviews, and machining operation time is estimated by using empirical formulas derived from the actual shop floor data. A case example of split cavity plate is used to demonstrate the system performance. ？ 1994.